Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1073/pnas.241184198
|View full text |Cite
|
Sign up to set email alerts
|

FRAP/mTOR is required for proliferation and patterning during embryonic development in the mouse

Abstract: The FKBP-12-rapamycin associated protein (FRAP, also known as mTOR and RAFT-1) is a member of the phosphoinositide kinase related kinase family. FRAP has serine͞threonine kinase activity and mediates the cellular response to mitogens through signaling to p70s6 kinase (p70 s6k ) and 4E-BP1, resulting in an increase in translation of subsets of cellular mRNAs. Translational up-regulation is blocked by inactivation of FRAP signaling by rapamycin, resulting in G 1 cell cycle arrest. Rapamycin is used as an immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
139
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 22 publications
17
139
1
Order By: Relevance
“…mTOR is normally expressed by progenitors in the developing telencephalon (Hentges et al, 2001). In the mouse mutant flat-top, mTOR function in the developing telencephalon is reduced, as is proliferation (Hentges et al, 1999(Hentges et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mTOR is normally expressed by progenitors in the developing telencephalon (Hentges et al, 2001). In the mouse mutant flat-top, mTOR function in the developing telencephalon is reduced, as is proliferation (Hentges et al, 1999(Hentges et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is normally expressed by progenitors in the developing telencephalon (Hentges et al, 2001). In the mouse mutant flat-top, mTOR function in the developing telencephalon is reduced, as is proliferation (Hentges et al, 1999(Hentges et al, , 2001. A similar phenotype was observed after rapamycin treatment in utero at early stages of development (Hentges et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Akt/mTOR pathway has been shown to regulate cell-cycle progression, as inhibition of this pathway can result in G1 cell-cycle arrest (Wiederrecht et al, 1995;Hentges et al, 2001). We have previously shown that U-251 cells treated with PMA for 24 h resulted in a striking increase in PKC-Z protein levels (Hussaini et al, 2000).…”
Section: H-thymidine Uptakementioning
confidence: 98%
“…Moreover, it is imperative to identify the downstream targets and cellular processes that are regulated by TOR. TOR function is clearly vitally important in mammals, as homozygous mTOR inactivation in the mouse is embryonically lethal (Hentges et al, 2001).…”
Section: Future Directionsmentioning
confidence: 99%